Overall Survival by Response to First-line Induction Treatment with Atezolizumab plus Platinum-based Chemotherapy or Placebo plus Platinum-based Chemotherapy for Metastatic Urothelial Carcinoma - Enrique Grande; Aristotelis Bamias; Matthew D. Galsky; Eiji Kikuchi; Ian D. Davis; José Ángel Arranz; Arash Rezazadeh Kalebasty; Xavier Garcia del Muro; Se Hoon Park; Ugo De Giorgi; Boris Alekseev; Marina Mencinger; et al. (European Urology Open Science, 2023)
Standard-of-care first-line treatment for metastatic urothelial carcinoma (mUC) is platinum-based chemotherapy (CTx). Maintenance immunotherapy is a treatment option for patients without progressive disease (PD) after induction CTx. IMvigor130 was a randomised, phase 3 study evaluating atezolizumab plus platinum-based CTx (arm A), atezolizumab monotherapy (arm B), or placebo plus platinum-based CTx (arm C) as first-line treatment for mUC. The primary progression-free survival (PFS) analysis showed a statistically significant PFS benefit favouring arm A versus arm C, which did not translate into overall survival (OS) benefit at the final OS analysis. We report exploratory analyses based on response to combination induction treatment (arm A vs arm C) using final OS data. Post-induction OS was analysed for patients without PD during induction (4–6 CTx cycles) who received at least one dose of single-agent atezolizumab/placebo maintenance treatment. Post-progression OS was analysed for patients with PD during induction CTx. Addition of atezolizumab to CTx did not impact OS outcomes, regardless of response to induction CTx, with hazard ratios of 0.84 (95% confidence interval [CI] 0.63–1.10) for patients without PD and 0.75 (95% CI 0.54–1.05) for those with PD during induction CTx. Treatment effects appeared to be greatest for patients treated with cisplatin and for those with PD-L1–high tumours. Patient summary: The IMvigor130 trial showed that addition of atezolizumab to chemotherapy (CTx) did not improve survival over CTx alone in patients with bladder cancer. Overall, patients whose cancer did not progress during initial treatment tended to live longer than patients whose cancer did progress, but addition of atezolizumab to CTx did not help either group live longer in comparison to CTx alone. However, the results suggest that patients who received a certain CTx drug (cisplatin) or who had high levels of a marker called PD-L1 in their tumour may get the most improvement from addition of atezolizumab to CTx.The IMvigor130 trial is registered on ClinicalTrials.gov as NCT02807636.